Direct Conversion of Polypropylene into Liquid Hydrocarbons on Carbon‐Supported Platinum Catalysts. Issue 23 (22nd October 2021) - Jaydev, Shibashish D.; Martín, Antonio J.; Pérez‐Ramírez, Javier
Abstract: Efforts to selectively convert polypropylene (≈30 % of all plastic waste) have not been particularly successful. Typical distributions span from gas to solid products, highlighting a challenging cleavage control. Here, carbon‐supported platinum nanoparticles were designed for complete hydrocracking into liquid hydrocarbons (C5 –C45 ). The metal and carrier phases operated synergistically. The cleavage activity depended on platinum and its rate rose with decreasing particle size. The carbon carrier controlled selectivity via hydrocarbon binding strength, which depended on the chain length and on the surface oxygen concentration. An optimal binding provided by carbons with high oxygen content promoted both adsorption of long chains and desorption of short products. This strategy achieved an unprecedented 80 % selectivity toward motor oil (C21 –C45 ). Carbons exhibiting too strong binding (low oxygen content) hindered product desorption, while non‐binding materials (e. g., silica or alumina) did not promote plastic–Pt contact, leading in both cases to low performance. This work pioneers design guidelines in a key process towards a sustainable plastic economy. Abstract : Plastics recycling : Complete conversion of polypropylene into liquid hydrocarbons with high selectivity for motor oil is promoted by carbon‐supported platinum catalysts. Activity is dependent on the metal nanoparticle size, whereas selectivity is governed by hydrocarbons' adsorption strength on the carbon carrier; the latter being tunable via the concentration of surface oxygen atoms.